THE EXERCISE POWER OF CAPITOL IN PANEM AS AMBIGUOUS UTOPIA CITY (TRILOGY HUNGER GAMES) - Yudhi Pratama Suardi (UIN Alauddin Makassar, 2017)
AbstractThis research discussed about the Exercise Power of Capitol in Panem as Ambiguous Utopia City in Trilogy Hunger Games Movies such as Hunger Games, Catching Fire, Mockingjay Part I and Part II. The aims of this research were to describe the processes of Capitol created Panem as Ambiguous Utopia City and to find out the forms of Ambiguous Utopia City in Panem. This research used post- colonialism approach by Upstone’s theory which describe about post space. This research applied descriptive qualitative method. This research used note taking as the instrument in order to get the valid data. The findings showed that the borders and orders were used by Capitol to create Panem as Ambiguous Utopia City and the findings also showed that there were three city forms in Panem such as Utopia, Nowhere, and Carnival City. The researcher concluded that Capitol as the central city which became the ambiguous Utopia City.AbstrakPenelitian ini membahas tentang Latihan Kekuatan Capitol di Panem sebagai Kota Utopia yang ambigu di Trilogy Hunger Games Movies seperti Hunger Games, Catching Fire, Mockingjay Bagian I dan Bagian II. Tujuan dari penelitian ini adalah untuk mendeskripsikan proses Capitol yang menciptakan Panem sebagai Kota Utopia yang ambigu dan untuk mengetahui bentuk Kota Utopia yang ambigu di Panem. Penelitian ini menggunakan pendekatan pasca kolonialisme dengan teori Upstone yang menggambarkan tentang ruang pos. Penelitian ini menggunakan metode deskriptif kualitatif. Penelitian ini menggunakan catatan sebagai instrumen untuk mendapatkan data yang valid. Temuan menunjukkan bahwa perbatasan dan perintah digunakan oleh Capitol untuk menciptakan Panem sebagai Kota Utopia yang ambigu dan temuan tersebut juga menunjukkan bahwa ada tiga bentuk kota di Panem seperti Utopia, Nowhere, dan Carnival City. Peneliti menyimpulkan bahwa Capitol sebagai pusat kota yang menjadi Kota Utopia yang ambigu.